التسمم الغذائي ببكتيريا السالمونيلا: دراسة ميدانية تحليلية لتقييم وعي الأطباء بالمخاطر الصحية وإدراكهم لاستراتيجيات الوقاية مستشفى صبراتة التعليمي نموذجًا (Al-Farooq Journal of Sciences, 2026)
This study aimed to assess physicians’ awareness of the health risks associated with food poisoning caused by Salmonella bacteria and their awareness of prevention strategies at Sabratha Teaching Hospital. The study adopted the descriptive analytical method and used a questionnaire as the main data collection tool. The questionnaire was administered to a purposive sample of 20 physicians from the internal medicine and pediatrics departments. The findings showed that the participants had a high level of awareness of the seriousness of food poisoning caused by Salmonella, as well as the importance of proper cooking and hygiene in reducing infection transmission. The results also revealed clear awareness of the disease risk among children and the elderly, with some variation in certain detailed scientific aspects related to bacterial strains and sources of food contamination. The study recommended strengthening training and awareness programs for physicians and supporting food safety procedures in healthcare institutions.
Keywords: Food poisoning, Salmonella, health awareness, physicians, prevention, Sabratha Teaching Hospital